2010
DOI: 10.1074/jbc.m109.080358
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Class I Tagatose-1,6-bisphosphate Aldolase

Abstract: Tagatose-1,6-bisphosphate aldolase from Streptococcus pyogenes is a class I aldolase that exhibits a remarkable lack of chiral discrimination with respect to the configuration of hydroxyl groups at both C3 and C4 positions. The enzyme catalyzes the reversible cleavage of four diastereoisomers (fructose 1,6-bisphosphate (FBP), psicose 1,6-bisphosphate, sorbose 1,6-bisphosphate, and tagatose 1,6-bisphosphate) to dihydroxyacetone phosphate (DHAP) and D-glyceraldehyde 3-phosphate with high catalytic efficiency. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The three-dimensional structure and mechanism of action of tagatose-6-phosphate kinase (LacC) [14] and of class I and II tagatose-1,6-diphosphate aldolase (LacD) [15,16] have been investigated using X-ray crystallography techniques. Galactose-6-phosphate isomerase (LacAB), which is a heteromultimer of LacA and LacB subunits, has been cloned, expressed in E.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional structure and mechanism of action of tagatose-6-phosphate kinase (LacC) [14] and of class I and II tagatose-1,6-diphosphate aldolase (LacD) [15,16] have been investigated using X-ray crystallography techniques. Galactose-6-phosphate isomerase (LacAB), which is a heteromultimer of LacA and LacB subunits, has been cloned, expressed in E.…”
Section: Introductionmentioning
confidence: 99%
“…This correlates with numerous observations using FruA and other DHAP-dependent aldolases, for which hydroxylation at the 2-or 3-position facilitates the correct binding of the aldehyde electrophile in the active site. [16,31] It became evident from X-ray studies of DHAP aldolases that the absolute stereospecificity of the configuration at the nucleophilic carbon usually is fully controlled by the enzyme as stereospecific deprotonation is assisted by hydrogen bonding of the hydroxy group to give a cis or trans enediolate (or hydroxyenamine equivalent) with spatial protection of one prochiral hemisphere of the "carbanion" equivalent from the protein backbone. Diastereoselectivity results from two-fold hydrogen bonding of the aldehyde carbonyl by active-site residues to activate and correctly position the electrophilic center for stereoselective attack by the enolate (or enamine) nucleophile with retention of its configuration.…”
mentioning
confidence: 99%
“…Interestingly, it has been observed that tagatose aldolase from Staphylococcus aureus is able to catalyze the aldol addition of DHAP to d-glyceraldehyde-3-phosphate to produce a mixture of the 1,6-diphosphate derivatives of d-tagatose, d-fructose, d-sorbose, and d-psicose [96]. A similar stereoselective behavior has been observed in TagA from Streptococcus pyogenes [97]. Investigations on the structure and mechanism of this aldolase revealed that its lack of chiral discrimination with respect to the configuration of hydroxyl groups at C-3 position, the most conserved in the aldolases known, is given by the ability of the enzyme to interchange the cis (Scheme 8.27a) and trans (Scheme 8.27b) isomers with respect to the DHAP C2-Lys205 N ε bond of the intermediate enzyme-DHAP carbanion mesomer (Scheme 8.27).…”
Section: Structure and Mechanismmentioning
confidence: 62%